Pemilihan Moda Transportasi Umum Cilegon–Merak Menggunakan Metode Analytic Hierarchy Process - Laska Hevanda; Muhammad Oka Mahendra (Institut Teknologi Garut, 2025)
This study aims to determine the most optimal public transportation mode used by the public on the Cilegon-Merak route. The approach used is the Analytic Hierarchy Process (AHP) method by considering seven main criteria, namely: travel time, cost, comfort, safety, accessibility, punctuality, and availability of modes. Data were collected by distributing questionnaires to a number of stakeholders, including transportation users, Transportation Agency officers, academics, and railway officers. The results of the analysis show that local trains are the most optimal mode of transportation, indicated by the highest global score of 4.34, followed by buses and public transportation. These findings provide recommendations for policy makers to improve train services as the mainstay transportation in the Cilegon-Merak corridor.